Pfcrt mutant haplotypes may not correspond with chloroquine resistance - Diganta Goswami; Sunil Dhiman; Bipul Rabha; Dinesh Kumar; Indra Baruah; Dhirendra Kumar Sharma; Vijay Veer (Journal of Infection in Developing Countries)
Introduction: Chloroquine resistance in Plasmodium falciparum is associated with mutations in pfcrt and pfmdr1 genes. The frequency distribution of pfcrt K76T and pfmdr1 N86Y mutations and their association with chloroquine susceptibility was studied in an endemic area along the Indo-Bangladesh border. Methodology: A single-arm prospective study of clinical and parasitological responses in P. falciparum malaria patients to chloroquine was conducted in vivo. PCR-RFLP assay was used to detect pfcrt K76T and pfmdr1 N86Y mutations in P. falciparum. The PCR products of pfcrt gene were sequenced,  translated and aligned for haplotyping. Results: Out of 63 cases, 44 (69.8%) responded adequately to chloroquine treatment. Pfcrt K76T mutation was recorded in 100% of the treatment failure cases, whereas pfmdr1 N86Y mutation was found in 52.6% of the cases only. Early treatment failure (84.2%) occurred more frequently than late treatment failure (15.8%). Kaplan–Meier survival analysis showed that the probability estimate for treatment success after 7 and 15 days was 0.84 (95% CI = 0.72-0.92) and 0.70 (95% CI = 0.57-0.80), respectively. Sequence analysis of 72 to 76 pfcrt gene codons revealed the presence of two mutant (CVMNT, CVIET) and two wild (CVMNK, CVIEK) haplotypes. The mutant CVIET haplotype was predominantly distributed (42.1%). Conclusions: The presence of mutations in pfcrt K76T and pfmdr1 N86Y genes is not sufficient to explain the therapeutic efficacy of chloroquine to P. falciparum. Study suggests that pfcrt K76T mutant haplotypes are widely distributed and are spreading diligently, which needs to be taken into account in devising an antimalarial policy.